Evaluation of teachers’ self-efficacy on integration of eye health education and promotion at basic schools in Solukhumbu district, Nepal: A cross-sectional study - Basnet, Pushpa Babu; Budhathoki, Chitra Bahadur; Khanal, Shanti Prasad; Acharya, Jib; Pathak, Krishna Prasad (Nepalese Journal of Ophthalmology, 2022)
Introduction: Many studies have shown that eye health services in Nepal are still far behind in reaching schools. Therefore, the aim of this study is to examine the teacher’s self-efficacy for the incorporation of eye health promotion activities. Materials and methods: A cross-sectional study design was applied with a self-administrated questionnaire. A total of 292 teachers were randomly selected for this study. Results: Male (153.38) older-aged and Dalit ethnic group (159.81) teachers, as well as teachers who had participated (146.85) in the program, had higher self-efficacy to conduct school eye health-promoting activities than non-participants in schools. But, teaching experience is not determined to get self-efficacy for testing of visual acuity. Teachers with higher qualifications are found to be skillful. Conclusion: The school’s eye health program has not been superseded by any relevant legislation. As a result, it’s critical to concentrate on provisions that may be included in the school curriculum.